Physical education teachers’ attitudes toward inclusion of students with disabilities in Saudi Arabia - Alhumaid, Majed M.; Althikr Allah, Bashaer A.; Alhuwail, Abeer A.; Alobaid, Maryam A.; Abu Hamad, Naflah N.; Alsalman, Zainab A.; Alqahtani, Sarah S.; Alherz, Ayat M.; Alwael, Walla M.; Alhelal, Aeshah K.; Alsubaie, Sheikh A.; Alwarthan, Maryam S.; et al. (Frontiers in Psychology, 2022)
The attitudes of physical education (PE) teachers towards inclusion are critical to the successful provision of inclusive teaching for students with disabilities. Therefore, the purpose of this study was to investigate the attitudes of Saudi Arabian PE teachers towards the inclusion of students with disabilities in PE classes and the effect of sociodemographic variables (e.g., gender and length of teaching experience) on their attitudes towards inclusion. A total of 1,314 PE teachers (Mage = 41.09, SD = 9.40, females = 42.8%) completed the Arabic version of the Sentiments, Attitudes, and Concerns about Inclusive Education-Revised Scale (SACIE-R). Analyses found that, in general, PE teachers had moderately positive attitudes toward the inclusion of students with disabilities in PE lessons. A significant difference was found between the two genders in their attitudes toward inclusion. Specifically, female PE teachers demonstrated more positive attitudes toward inclusion than males. Multiple linear regression analysis, meanwhile, showed that the length of teaching experience and the experience of teaching a student with a disability were significant predictors of participants' attitudes toward inclusion. Our findings highlighted the importance of reconsidering the quality of PE teachers’ experiences and interactions with students with disabilities as a means to improving their attitudes, which in turn would translate into successful inclusion.